Long-Term Effect of Half-Fluence Photodynamic Therapy on Fundus Autofluorescence in Acute Central Serous Chorioretinopathy - Martin Stattin; Stefan Hagen; Daniel Ahmed; Eva Smretschnig; Florian Frommlet; Katharina Krepler; Siamak Ansari-Shahrezaei (Journal of Ophthalmology)
Purpose. To evaluate normalized short-wavelength fundus autofluorescence (SW-FAF) imaging changes over time as a predictive parameter for the retinal pigment epithelium (RPE) function in eyes compromised by acute central serous chorioretinopathy (CSCR) after indocyanine green angiography-guided verteporfin (Visudyne®, Novartis Pharma, Basel, Switzerland) photodynamic therapy (PDT) with a half-fluence rate (25 J/cm2). Methods. Quantitative data of SW-FAF grey values (SW-FAF GV) from a 350 μm (SW-350) and 1200 μm (SW-1200) diameter circle centered on the fovea and normalized with the level of SW-FAF GV in a 30° image of 20 eyes in 11 patients initially treated for unilateral acute symptomatic CSCR were collected and retrospectively analyzed after 7 years. A 2-sided t-test was calculated to explore the differences of SW-350 and SW-1200 between one month and the long-term follow-up. Results. Mean differences (95% CI) in SW-FAF GV between 1 month and 7 years after half-fluence PDT were 0.07 ± 0.11 for SW-350 ([95% CI: −0.002; 0.14], p=0.06) and 0.11 ± 0.15 for SW-1200 ([95% CI: 0.01; 0.21], p=0.03). Mean differences in SW-FAF GV of the contralateral untreated eye were 0.06 ± 0.14 for SW-350 ([95% CI: −0.04; 0.17], p=0.22) and 0.05 ± 0.13 for SW-1200 ([95% CI: −0.04; 0.15], p=0.22). Conclusion. After 7 years, normalized SW-FAF GV were significantly lower in eyes with resolved acute CSCR treated with reduced-fluence PDT compared to the follow-up after 1 month without correlation to explicit pattern changes or structural damages. Half-fluence PDT remains a safe and considerable treatment option in acute CSCR.